2022
DOI: 10.1101/2022.12.15.520612
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accurate cell type deconvolution in spatial transcriptomics using a batch effect-free strategy

Abstract: Sequencing-based spatial transcriptomics (ST) techniques have been groundbreaking in dissecting cell-cell communications within tissues by profiling positional gene expression. However, the most widely used ST technique, Visium Spatial Gene Expression by 10x Genomics (Visium), does not provide single-cell resolution, making it difficult to profile cell type-level information. Many reference-based deconvolution methods have been developed to increase its resolution, but the platform and batch effects between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This unsupervised machine learning facilitates the mechanization of extracting relevant information from the GDC website and converting it into a matrix format. The research discovered noteworthy M(M+U) values, which represent methylated and unmethylated allele intensities, augmenting our comprehension of ESCA cancer and demonstrating the advantages of combining TCGAbiolinks and Enhancer Methylation/expression relationship [17, 18].…”
Section: Methodsmentioning
confidence: 99%
“…This unsupervised machine learning facilitates the mechanization of extracting relevant information from the GDC website and converting it into a matrix format. The research discovered noteworthy M(M+U) values, which represent methylated and unmethylated allele intensities, augmenting our comprehension of ESCA cancer and demonstrating the advantages of combining TCGAbiolinks and Enhancer Methylation/expression relationship [17, 18].…”
Section: Methodsmentioning
confidence: 99%
“…Another category of deconvolution methods, known as reference-free deconvolution methods, does not require single-cell transcriptomic data as a reference. Representative methods in this category include CARDfree [120], STdeconvolve [124], and SMART [125]. In spatial transcriptomic samples of tumors, the estimation of cancer cell abundance can be particularly challenging due to the heterogeneity of tumor cells.…”
Section: Deconvolutionmentioning
confidence: 99%
“…When one stimulus is strong, the perceived intensity of the other stimulus is weak. For example, an increase in hearing reduces the perception of smell, but an increase in smell increases the perception of hearing (Wang et al, 2022). Ba and Kang suggested that the type of odor, concentration of the odor, and different bird song volumes jointly affect overall comfort and consistency (Ba and Kang, 2019).…”
Section: Introductionmentioning
confidence: 99%